SISTEM PERENCANAAN, PELAKSANAAN DAN PENGAWASAN INDUSTRI HALAL DI WILAYAH PROVINSI BANTEN - Ahyakudin, A; Suja?i, S; Abduh, Muhammad (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Abstract. The role of the industrial sector in meeting the livelihoods of the people of Banten should be accompanied by efforts to develop an industrial system that prioritizes the halal value on its production. The development of the halal industry can be realized with a system of planning, implementation and supervision in accordance with the principle of halal thayyibah. The method that will be used in this research is descriptive qualitative. Information gathered from the initial research is expected to provide an overview and prescription of the relationship between the planning, implementation, and supervision of the implementation of the Halal Industry in Banten Province. The results of this study explain that aspects of industrial planning should pay attention to aspects of Maqashid Syariah and aspects of trust as an effort to provide certainty that industrial products are in accordance with halal provisions. In practice, industrial management should not only issue technical rules but must also be accompanied by qualifications of basic sharia knowledge in production activities. While in the aspect of supervision, the person in charge must have a deep understanding of the aspects of li dzatihi, li ghairihi, and li aqibatihi as the main components of the halal system. Constraints on halal industry development are experienced by micro and small businesses due to certification costs, inadequate halal industry governance, and fears of leakage of company product secrets.Abstrak: Peran sektor industri dalam memenuhi hajat hidup masyarakat Banten hendaknya harus dibarengi upaya pengembangan sistem Industri yang mengedepankan nilai halal pada produksinya. Pengembangan Industri halal dapat diwujudkan dengan sistem perencanaan, pelaksanaan dan pengawasan yang sesuai dengan prinsip halâlan thayyibah. Metode yang akan digunakan dalam penelitian ini ialah deskriptif kualitatif, Informasi yang tergali dari penelitian awal diharapkan dapat memberikan gambaran dan preskripsi hubungan antara sistem perencanaan, pelaksanaan, dan pengawasan terhadap penyelenggaraan Industri Halal di Provinsi Banten. Hasil penelitian ini menjelaskan bahwa aspek perencanaan industri hendaknya memperhatikan aspek maqashid Syariah dan aspek amanah sebagai upaya memberikan kepastian bahwa produk industri telah sesuai dengan ketentuan halal. Dalam pelaksanaannya, manajemen industri hendaknya tidak hanya mengeluarkan aturan-aturan tekhnis semata namun juga harus dibarengi dengan kualifikasi pengetahuan kesyariahan mendasar pada kegiatan produksi. Sedangkan dalam aspek pengawasan, penanggungjawab harus memiliki pemahaman mendalam pada aspek li dzatihi, li ghairihi, dan li aqibatihi sebagai komponen utama sistem halal. Kendala pengembangan Industri halal dialami oleh usaha mikro dan kecil dikarenakan biaya sertifikasi, tata kelola industri halal belum memadai, serta ketakutan akan bocornya rahasia produk perusahaan.